Features of dyslipidemia in people with different body mass - K.V. Misyura (Danylo Halytsky Lviv National Medical University, 2017)
Aim. To describe specific features of lipid metabolism in population of Kharkiv in relation to the body mass and composition; to study changes in its parameters associated with the topography of adipose tissue accumulation, presence and significance of insulin resistance; markers of metabolic disorders, local inflammation of adipose tissue, systemic low-intensity inflammation, and leptinemia level.